Does cooperation pay? The role of social capital among household plot farmers in Ukraine - Axel Wolz; Jana Fritzsch; Gertrud Buchenrieder; Andriy Nedoborovskyy (South East European Journal of Economics and Business, 2010)
Social capital matters, not the least in determining individual welfare. It is argued that it functions similar to traditional production factors. However, there are not many empirical analyses about this issue at the farm-household level in general and in post-communist countries in particular. Whether or not social capital affects farm income is tested using micro-data from 255 household plot farmers in Ukraine. The data reflect 23 social capital indicators. These are merged in four separate index variables. The index variables reflect the theoretical dimensions of social capital, namely form, i.e. structural and cognitive, and relationship, i.e. bonding and bridging. By adopting multiple regression analysis, it can be shown that social capital in the form of bridging is indeed a significant factor for determining the level of agricultural income. However, the findings also underline the multidimensional side of social capital. Both bonding and cognitive social capital show no immediate impact on agricultural income among household plot farmers in Ukraine.
Keywords: O13; P32; Q12; Z13; 330; empirical survey; household farming; agricultural income; social capital; Ukraine